Choice of Antihypertensive Combination Therapy Based on Daily Salt Intake. (September 2015) - Toyoda, Shigeru; Inami, Shu; Kato, Toru; Tsukada, Kinji; Nakamoto, Akiya; Kikegawa, Yoshinobu; Suzuki, Akihiro; Anraku, Yukitaka; Node, Koichi; Inoue, Teruo
Abstract: Background: It is unclear whether thiazide diuretics (TZs) or calcium channel blockers (CCBs) are more effective as add-on therapy to angiotensin receptor blockers (ARBs) in controlling hypertension. Because TZs are a rational choice in salt-sensitive hypertension, patients with high salt intake might preferentially benefit from ARB/TZ over ARB/CCB combination therapy. Methods: Hypertensive patients who failed to reach blood pressure goals despite treatment with ARBs alone were randomly assigned to receive either ARB/TZ or ARB/CCB combination therapy. Estimated daily sodium intake was calculated from spot urine values of sodium and creatinine. Results: Blood pressure was measured at baseline, and at 4, 8 and 12 weeks after starting combination therapy. For all study patients (n = 87), diastolic blood pressure reduction was greater in patients receiving ARB/CCB treatment. However, in the 37 patients with a baseline estimated daily salt intake greater than 10 g and baseline systolic blood pressure (SBP) ranging from 150 to 200 mm Hg, SBP was lower ( P < 0.05) and SBP reduction was greater ( P < 0.05) 4 weeks after starting combination therapy in those receiving ARB/TZ treatment. In the 31 patients whose estimated daily salt intake increased at 12 weeks compared with baseline, SBP at 12 weeks was lower in those receiving ARB/TZ treatment ( P < 0.05). Conclusions: Estimated daily salt intake is a useful tool for guiding antihypertensive therapy and should be measured repeatedly during the therapeutic course.